Penegakan Hukum Tindak Pidana Judi Online Oleh Kepolisian Daerah Istimewa Yogyakarta - Syahreva Smaradahana Fakayun Libasae; Wahyu Priyanka Nata Permana (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
Problems in the study related to the enforcement of online gambling criminal law by the DIY Regional Police and obstacles in the enforcement of online gambling criminal law by the DIY Regional Police. The purpose of this study is to determine the enforcement of online gambling criminal law by the DIY Regional Police. The research method uses empirical legal research. The approach method uses sociological juridical. Based on the research, the author concludes that the enforcement of online gambling criminal law by the DIY Regional Police is carried out with preemptive, preventive and repressive steps through the penal and non-penal channels. Obstacles in the enforcement of online gambling criminal law by the DIY Regional Police are caused by legal factors, law enforcement factors, facilities and infrastructure factors, community factors and cultural factors. The DIY Regional Police should be more persistent in implementing preemptive, preventive and repressive steps through the penal and non-penal channels. There are also updates related to the laws governing online gambling related to the media used to play gambling until the sanctions and punishments are increased.